On an integral involving H-function - Rathie, A. K. (Rev. Téc. Fac. Ing. Univ. Zulia, 1970)
In this paper an integral involving hyper geometric function and the H-function has been evaluated. The results are believed to be new. A few interesting particular cases have also been given.